2014
DOI: 10.3758/s13423-014-0765-4
|View full text |Cite
|
Sign up to set email alerts
|

When two heads are better than one: Interactive versus independent benefits of collaborative cognition

Abstract: Previous research has shown that two heads working together can outperform one working alone, but whether such benefits result from social interaction or from the statistical facilitation of independent responses is not clear. Here we apply Miller's (Cognitive Psychology, 14, 247-279, 1982; Ulrich, Miller & Schröter, Behavior Research Methods, 39(2), 291-302, 2007) race model inequality (RMI) to distinguish between these two possibilities. Pairs of participants completed a visual enumeration task, both as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(101 citation statements)
references
References 20 publications
5
87
1
Order By: Relevance
“…Taken together, previous studies investigating collective benefits in collaborative visuospatial tasks showed that exchanging information about the co-actors' performed actions leads to a high collective benefit (Brennan et al, 2008; Neider et al, 2010; Brennan and Enns, 2015; Wahn et al, 2016c). Other studies investigating collective benefits in a collaborative decision-making task showed that having performance scores available about the individual and co-actors' decisions can further increase an already existing collective benefit (Bahrami et al, 2010, 2012a).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Taken together, previous studies investigating collective benefits in collaborative visuospatial tasks showed that exchanging information about the co-actors' performed actions leads to a high collective benefit (Brennan et al, 2008; Neider et al, 2010; Brennan and Enns, 2015; Wahn et al, 2016c). Other studies investigating collective benefits in a collaborative decision-making task showed that having performance scores available about the individual and co-actors' decisions can further increase an already existing collective benefit (Bahrami et al, 2010, 2012a).…”
Section: Introductionsupporting
confidence: 52%
“…Collective benefits have been researched extensively in the past in several domains such as decision-making (Bahrami et al, 2010, 2012a,b), attention (Brennan et al, 2008; Neider et al, 2010; Wahn et al, 2016c; Brennan and Enns, 2015), or sensorimotor processing (Knoblich and Jordan, 2003; Masumoto and Inui, 2013; Ganesh et al, 2014; Rigoli et al, 2015; Skewes et al, 2015; Wahn et al, 2016b). This work has converged on the conclusion that several factors may influence if, and to what extent, groups outperform individuals (Knoblich and Jordan, 2003; Brennan et al, 2008; Bahrami et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Our work builds on recent findings on combining decisions, a research paradigm known as "two heads better than one" (15)(16)(17)(18)(19)(20). In their seminal study, Bahrami et al (15) showed that two individuals permitted to communicate freely while engaging in a visual perception task, achieved better results than the better of the two did alone.…”
mentioning
confidence: 76%
“…Others have shown that human groups can derive benefits by altering their individual decision strategies when searching for targets collaboratively (70)(71)(72). Future studies exploring collective wisdom for real world search tasks can explore whether groups adapt their joint decision algorithms to use more demanding averaging or weighted averaging procedures that obtain higher joint decision accuracies than the default majority voting procedure.…”
Section: Simple Majority Voting Obtains Inferior Wisdom Of Crowd Benementioning
confidence: 99%